2018
DOI: 10.2478/sgem-2018-0042
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a collapsible soil using a bentonite–cement mixture

Abstract: The study of collapsible soils that are generally encountered in arid and semi-arid regions remains a major issue for geotechnical engineers. This experimental study, carried out on soils reconstituted in the laboratory, aims firstly to present a method of reducing the collapse potential to an acceptable level by treating them with different levels of bentonite–cement mixture while maintaining the water content and degree of compactness, thus reducing eventual risks for the structures implanted on these soils.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Therefore, the destruction of intergranular bonds and movement of fine particles or grains leaching become relatively difficult. This can be confirmed by the results of Kinuthia et al, Abbeche et al, Bahloul et al [1,12,27] and Bellili et al [25].…”
Section: Influence Of Energy Compaction On the Collapse Potential Cpsupporting
confidence: 62%
See 1 more Smart Citation
“…Therefore, the destruction of intergranular bonds and movement of fine particles or grains leaching become relatively difficult. This can be confirmed by the results of Kinuthia et al, Abbeche et al, Bahloul et al [1,12,27] and Bellili et al [25].…”
Section: Influence Of Energy Compaction On the Collapse Potential Cpsupporting
confidence: 62%
“…Another study showed that the additional load and maximum negative skin friction due to the compacting effect of the battered pile, has a negative correlation with the amount of collapse, also the collapsibility rate of loess is affected by natural moisture content and dry density; hence collapse can be improved by an additional loading and a pre-wetting to reduce the harmful effect of the negative friction of the skin on the pile foundations, these results are carried out by Xing et al [24]. Studies evaluate the treatment of this type of soil with a mixture of bentonite and cement [25] or with natural pozzolan and slag mixture [26]. In order to achieve sustainable development, equilibrium must be found between the environmental, economic, social and technological systems and contribute to the maximum growth of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…The cohesion values increases and the angle of internal friction values decreases. The cohesion increase may be due to the high concentration of the minerals existing in textile sludge such as Aluminum, Calcium, and Magnesium as described before in Table 2, this minerals form a cementation bonds between soil particles, In addition, a decrease in the friction angle can be explained by the growth of the cohesive admixtures [20,21] Also the reduction of maximum dry density has a role in decreasing friction angle and consequently the soil bearing capacity.…”
Section: E Direct Shear Resultsmentioning
confidence: 99%
“…Today, world practice uses different methods and ways to eliminate collapsible properties of soils, including compaction, consolidation, and the use of soil cushions [13]. Methods such as onesolution silicification [14], thermal firing [15], and fiber [16] can be used to consolidate collapsible soils. The construction of a ground cushion creates a layer of non-collapsible soil in the foundation base.…”
Section: Introductionmentioning
confidence: 99%